2020
DOI: 10.30950/jcer.v16i2.1073
|View full text |Cite
|
Sign up to set email alerts
|

Irreconcilable Tensions? The EU’s Development Policy in an Era of Global Illiberalism.

Abstract: There have always been tensions within the EU's external development policy between ethical and self-interested approaches and also between universalist and realpolitik policies. The EU's structural economic power and global neoliberal dominance have allowed these tensions to be subsumed within its external policies. A range of factors has contributed to the rise of illiberalism globally, leading to heightened geoeconomic rivalry while complex changes in global development governance facilitate the use of aid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…In particular, the shift of Official Development Assistance (ODA) from the public to the private sector and replacing ODA with private finance has policy implications (Eurodad, 2013). Aside from limited evidence to show that blending mechanisms meet sustainable development objectives, value addition of grants and transparency in the decision-making process (Ferrer et al, 2012as cited by Romero, 2016; the increasing political interest clouding choices of countries where blended finances are applied, conflicting with the poverty reduction and global development objectives has been a source of concern (Holden, 2020). Previous work carried out by European Commission (2016) and International Finance Corporation -IFC (2017) reported that ODA dedicated to blending saw 77% of pooled investments concentrated in highly profitable sectors.…”
Section: Blended Finance: Potential Fencesmentioning
confidence: 99%
“…In particular, the shift of Official Development Assistance (ODA) from the public to the private sector and replacing ODA with private finance has policy implications (Eurodad, 2013). Aside from limited evidence to show that blending mechanisms meet sustainable development objectives, value addition of grants and transparency in the decision-making process (Ferrer et al, 2012as cited by Romero, 2016; the increasing political interest clouding choices of countries where blended finances are applied, conflicting with the poverty reduction and global development objectives has been a source of concern (Holden, 2020). Previous work carried out by European Commission (2016) and International Finance Corporation -IFC (2017) reported that ODA dedicated to blending saw 77% of pooled investments concentrated in highly profitable sectors.…”
Section: Blended Finance: Potential Fencesmentioning
confidence: 99%
“…The third group of motives is environmental, which can be of both altruistic and interest nature, driven by certain political, economic, or strategic interest (Gupta and Thompson, 2010). The discussion on the evolution of the EU development policy in literature follows that typology, and the debate is mostly concentrated on the dichotomy between "moral" and "selfish" motivation, or between "solidarity" and "instrumentality" (see, e.g., Furness et al 2020;Fukuda-Parr and McNeill 2019;Delputte and and Lighfoot 2019;Holden 2020;Szent-Iványi and Kugiel 2020;Babarinde 2019;Hadfield 2007).…”
Section: Theorising the Evolution Of The Eu Development Policy -From ...mentioning
confidence: 99%
“…Positive results by the 2014-2020 Partnership Instrument for example showcase how further work in this area can be continued; aligning the goals of the Global Public Goods and Challenges programme (GPGC) 2 with the growing needs of climate-driven sustainable development is another possibility, while embedding the original goals of the abovementioned Instrument contributing to Stability and Peace within emergency funding structures. Also visible is the shift in terms of instruments, such as the European Fund for Sustainable Development and broader attempts to leverage private sector finance for development ends (Holden, 2020). EU energy diplomacy for example aims to accelerate the global energy transition, while ensuring affordability, safeguarding the environment and achieving the SDGs.…”
Section: Climate Change and Energymentioning
confidence: 99%